Вплив виробничих ризиків на безпечність виробничих процесів: аналіз та прогнозування - Зоря, М. В.; Райко, Валентина Федорівна; Янчик, Олександр Григорович (Державний автотранспортний науково-дослідний і проектний інститут, 2024)
Дослідження зосереджене на аналізі виробничих ризиків у сфері управління підприємством. Виробничий ризик описаний як імовірність виникнення небажаних подій, що можуть призвести до відхилень від очікуваних результатів через різноманітні управлінські рішення. Основними характеристиками такого ризику є його варіативність та невизначеність. У статті представлено логічну модель управління виробничими ризиками та її інтеграцію з системою управління основними фондами підприємства. На прикладі цієї моделі продемонстровано опис входу, виходу та процесу моделювання. Входові дані охоплюють показники витрат на роботи з основними засобами та бюджетні обмеження. Для оцінки рівня ризику та його порівняльного аналізу було запропоновано метод індексів, який передбачає розрахунок індексу виробничого ризику для кожного виду виробничих ресурсів з метою визначення пріоритетності робіт. У статті також обговорюються шкали оцінки ймовірності виробничого ризику та впливу його наслідків, розроблені на основі математичного прогнозування.

The study is focused on the analysis of production risks in the field of enterprise management. Production risk is described as the probability of occurrence of undesirable events that may lead to deviations from expected results due to various management decisions. The main characteristics of such a risk are its variability and uncertainty. Risk management is defined as a procedure that includes all aspects of the company's activities, starting with the formation of a strategy and ending with the control of acceptable risks in order to achieve the set goals. The management process covers the identification of events that may adversely affect the production process and their proper management. The article presents a logical model of production risk management and its integration with the management system of the company's fixed assets. To assess the level of risk and its comparative analysis, the index method was proposed, which involves the calculation of the production risk index for each type of production resources in order to determine the priority of work. The article also discusses the scales for assessing the probability of production risk and the impact of its consequences, developed on the basis of mathematical forecasting. These scales can be adapted taking into account the opinions of experts and collected data. The article reveals how enterprise resources are prioritized taking into account production risk and budget constraints. This includes developing asset maintenance and repair cost plans, as well as updating the risk register and creating a probability and consequence matrix. An important feature of the model is its difference from existing approaches to the distribution of production resources, which includes the use of a formalized criterion for priority selection of works.
The influence of production risks on the safety of production processes: analysis and forecasting
Keywords: підприємство; виробничий ризик; прогнозування ризику; виробничий процес; системний підхід; управління ризиками; аналіз та оцінка ризику виробничої діяльності; enterprise; production risk; risk forecasting; production process; systematic approach; risk management; analysis and assessment of the risk of production activity